Pengembangan Media Pembelajaran Berbasis Lingkungan menggunakan Genially - Mulyasaroh; Yayat Ruhiat; Aan Hendrayana (Jurnal Penelitian Pendidikan IPA, 2026)
Science learning in elementary schools still faces challenges because ecosystem concepts are abstract and difficult for students at the concrete operational stage to understand. This study aimed to develop environment-based interactive learning media using the Genially platform and examine its effectiveness in improving students’ understanding of ecosystem concepts. This research employed a Research and Development (R&D) method using the ADDIE model, including analysis, design, development, implementation, and evaluation stages. The development phase resulted in interactive media integrating visual illustrations, animations, ecosystem simulations, and gamified quizzes. The product was validated by subject matter experts and media experts, obtaining scores of 92% and 93%, respectively, categorized as very suitable. The trial was conducted using a purposive sampling technique with 31 fifth-grade students at Pasar Bunder Elementary School, Cilegon City. Data were analyzed using descriptive statistics and the N-Gain test. The results showed that the average score increased from 50 (pretest) to 86 (posttest), with an N-Gain value of 0.72 (high category). In conclusion, the developed Genially-based learning media is effective in improving students’ understanding of ecosystem concepts through interactive and visual representations of environmental contexts.